Development and physiological effects of an artificial diet for Wolbachia-infected Aedes aegypti. Issue 1 (December 2017) - Dutra, Heverton; Rodrigues, Silvia; Mansur, Simone; Oliveira, Sofia; Caragata, Eric; Moreira, Luciano
Abstract The endosymbiotic bacteriumWolbachia spreads rapidly through populations ofAedes aegypti mosquitoes, and strongly inhibits infection with key human pathogens including the dengue and Zika viruses. Mosquito control programs aimed at limiting transmission of these viruses are ongoing in multiple countries, yet there is a dearth of mass rearing infrastructure specific toWolbachia -infected mosquitoes. One example is the lack of a blood meal substitute, which accounts for theWolbachia -specific physiological changes in infected mosquitoes, that allows the bacterium to spread, and block viral infections. To that end, we have developed a blood meal substitute specifically for mosquitoes infected with thew MelWolbachia strain. This diet, ADM, contains milk protein, and infant formula, dissolved in a mixture of bovine red blood cells and Aedes physiological saline, with ATP as a phagostimulant. Feeding with ADM leads to high levels of viable egg production, but also does not affect keyWolbachia parameters including, bacterial density, cytoplasmic incompatibility, or resistance to infection with Zika virus. ADM represents an effective substitute for human blood, which could potentially be used for the mass rearing ofw Mel-infectedA. aegypti, and could easily be optimized in the future to improve performance.